THE IMPLICATIONS OF VIRTUAL COMMUNICATION IN MANAGING THE COVID-19 PANDEMIC NEW CULTURAL NORMS: A CASE STUDY IN THE NORTHWEST COAST OF SABAH - Halina Sendera Mohd Yakin; Kwan Yien Yee; Odetta Yahcob; Andreas Totu; Suraya Sintang; Siti Hasnah Tanalol (Journal of Islamic, Social, Economics and Development, 2021)
The Covid-19 pandemic that swept people across the world brings an inevitable impact on various aspects of life. This has sparked a new norm that promotes the importance as well as the need and dependence on virtual communication for the social life that is no longer compatible with the old norms that are conventional in nature. The main objective of this paper is to examine the implications of virtual communication on rural communities in Sabah during the Covid-19 pandemic by identifying the forms of challenges, contributing factors and adaptation mechanisms that are being practiced. Field studies were conducted at Kudat, Kota Marudu and Pitas districts in North West Coast of Sabah, Malaysia using the combination of both qualitative and quantitative methods, namely participant observation, interviews and questionnaire. The findings found that the challenges or problems faced by the community that are related to the implications of virtual communication involve aspects of teaching and learning, online transactions, career-related matters, daily routines and social relationships. Apart from physical factors such as hill landforms and forest-covered terrain, other factors such as economic status, social relationships, administrative enforcement as well as personal aspects such as perceptions, motivation and individual skills also have a significant impact on the challenges and problems of virtual communication among the rural communities. Individuals and organization involved have taken initiatives and implemented several strategies to address these issues. It is hoped that the findings of this paper can contribute useful recommendations with regard to the implications of virtual communication to all parties concerned in dealing with any related issues in the future.